An Untapped Potential in Primary Care: Semi-Structured Interviews with Clinicians on How Patient Portals Will Work for Caregivers in the Safety Net - Casillas, Alejandra; Cemballi, Anupama Gunshekar; Abhat, Anshu; Lemberg, Miya; Portz, Jennifer D; Sadasivaiah, Shobha; Ratanawongsa, Neda; Semere, Wagahta; Brown, Arleen; Lyles, Courtney Rees (JMIR Publications, 2020)
BackgroundPatients within safety-net settings are less likely to access health information on patient portals, despite expressed interest. Family and friends are important resources to assist these patients (ie, Medicaid recipients, older patients, patients with limited English proficiency) in navigating health systems, and provider support of the use of patient portals among these groups may also facilitate caregivers' use of their patients' portal. ObjectiveBecause safety net providers work closely with caregivers to care for their patients, we used qualitative methods to explore safety net providers' perspectives on portal use among caregivers for their patients, especially as there is limited literature about caregivers' use of portals in the safety net. MethodsWe conducted 45- to 60-min semistructured telephone interviews with providers from three large California safety-net health systems. The interviews focused on providers' experiences with caregivers, caregiver roles, and how the portal could be leveraged as a tool to support caregivers in their responsibilities. A total of three coders analyzed the interview transcripts using both deductive and inductive approaches and established a consensus regarding major themes. ResultsOf the 16 participants interviewed, 4 specialized in geriatrics, and all held a leadership or administrative role. We described themes highlighting providers' recognition of potential benefits associated with caregiver portal use and specific challenges to caregiver engagement. ConclusionsProviders recognized the potential for portals to improve information delivery and communication by helping caregivers assist socially and medically complex patients in the safety net. Providers in safety net sites also discussed a clear need for better ways to keep in touch with patients and connect with caregivers, yet security and privacy are perhaps of higher importance in these settings and may pose challenges to portal adoption. They noted that caregivers of patients in the safety net likely face similar communication barriers as patients, especially with respect to digital literacy, health literacy, and English proficiency. Further research is needed to assess and support caregivers' interest and ability to access portals across barriers in health and digital literacy, and English proficiency. Portal platforms and health systems must also address specific strategies to uphold patient preferences while maintaining privacy and security.